Regiochemistry Control by Bipyridine Substituents in the Deprotonation of ReI and MoIIN‐Alkylimidazole Complexes. Issue 39 (24th June 2019) - Espinal‐Viguri, Maialen; Fombona, Sergio; Álvarez, Daniel; Díaz, Jesús; Menéndez, M. Isabel; López, Ramón; Pérez, Julio; Riera, Lucía
Abstract: Compounds containing N ‐alkylimidazoles ( N ‐RIm) and 4, 4′‐disubstituted 2, 2′‐bipyridines (4, 4′‐R′2 bipy) coordinated to cationic Mo(η 3 ‐C4 H7 )(CO)2 and Re(CO)3 fragments undergo deprotonation of the C2‐H group of the N ‐RIm ligands in their reactions with KN(SiMe3 )2 . The resulting internal nucleophile adds either to one pyridyl ring, which becomes dearomatized and can undergo ring opening in the subsequent reaction with excess MeOTf, or to the metal center, yielding imidazol‐2‐yl complexes, which in turn add HOTf or MeOTf, affording N‐heterocyclic carbene complexes. Which pathway is followed is dictated by the metal and the nature of the imidazole (R) and bipyridine (R′) substituents. For Re I compounds, addition to pyridine is found with R′= t Bu and OMe, whereas for R=Me and R′=NMe2, imidazolyl formation is preferred. Coordination of 4, 7‐Cl2 ‐1, 10‐phenanthroline to Mo II favors C−C coupling, in contrast to the analogous parent bipy or phenanthroline complexes, for which formation of the imidazol‐2‐yl complexes had been found. DFT calculations showed the theoretically expected products in each case, and following their predictions new types of products were obtained experimentally. Abstract : Means to an end : The nature of the substituents at the backbone of α‐diimine ligands (4, 4′‐disubstituted‐2, 2′‐bipyridine or 2, 9‐disubstituted‐1, 10‐phenanthroline) is crucial to determining the type of product obtained on deprotonation of cationic N ‐alkylimidazole Mo II and Re I complexes (see figure for rhenium N ‐methylimidazole species).